2018
DOI: 10.1007/s11626-018-0239-5
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate induces cell death by autophagy and reactivates a tumor suppressor gene DIRAS1 in renal cell carcinoma cell line UOK146

Abstract: Sodium butyrate (SB), a histone deacetylase inhibitor, is emerging as a potent anti-cancer drug for different types of cancers. In the present study, anti-cancer activity of SB in Xp11.2 (TFE3) translocated renal cell carcinoma cell line UOK146 was studied. Anti-proliferative effect of SB in renal cell carcinoma (RCC) cell line UOK146 was evaluated by MTT assay and morphological characteristics were observed by phase contrast microscopy which displayed the cell death after SB treatment. SB induces DNA fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This is explained by a metabolic shift occurring in cancerous cells using preferentially glucose as the energy source. The inhibition of cell proliferation is generally characterised by an increase in reactive oxygen species production, DNA damages and cell cycle arrest, suggesting that SCFA initiate apoptosis signalling in cancer cells (93–96) . Indeed, through the activation of the pro-apoptotic protein BAX, the upregulation of apoptosis-inducing factor-mitochondria associated 1 isoform 6 and the reduction of mitochondrial membrane potential, SCFA stimulate the cytochrome c release which drives caspase 3 activation (93) .…”
Section: Functional Impact Of Scfa On the Hostmentioning
confidence: 99%
“…This is explained by a metabolic shift occurring in cancerous cells using preferentially glucose as the energy source. The inhibition of cell proliferation is generally characterised by an increase in reactive oxygen species production, DNA damages and cell cycle arrest, suggesting that SCFA initiate apoptosis signalling in cancer cells (93–96) . Indeed, through the activation of the pro-apoptotic protein BAX, the upregulation of apoptosis-inducing factor-mitochondria associated 1 isoform 6 and the reduction of mitochondrial membrane potential, SCFA stimulate the cytochrome c release which drives caspase 3 activation (93) .…”
Section: Functional Impact Of Scfa On the Hostmentioning
confidence: 99%
“…[8][9][10] NaB has been found to inhibit cell proliferation and migration of colorectal cancer, promote CRC cell apoptosis and induce autophagy and cell death. [10][11][12][13][14] The previously reported the correlation between NaB and Oxidative stress. 15 Numerous studies have shown that NaB significantly induces reactive oxygen species (ROS)mediated apoptosis in a variety of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that microtubule‐associated protein family 1 (MAP1S) can promote autophagy clearance of lipid droplets and reduce DNA double‐strand breaks and genome instability, consequently suppressing the development of ccRCC and promoting patient survival . Similarly, other groups have shown that autophagy can suppress ccRCC development . Therefore, whether autophagy promotes or inhibits cancer development or whether autophagy has different regulatory mechanisms for cancer development in different tissues requires further investigation …”
Section: Introductionmentioning
confidence: 99%
“…19 Similarly, other groups have shown that autophagy can suppress ccRCC development. [20][21][22] Therefore, whether autophagy promotes or inhibits cancer development or whether autophagy has different regulatory mechanisms for cancer development in different tissues requires further investigation. 9,23 Mitochondrial E3 ubiquitin ligase 1 (Mul1), a multifunctional mitochondrial membrane-associated protein located on the outer membrane of the mitochondrion with two transmembrane domains and one Ring-finger domain, 24 regulates different biological processes such as mitochondrial dynamics, cell growth, apoptosis and mitophagy (autophagy degradation of mitochondria), through ubiquitination and SUMOylation.…”
Section: Introductionmentioning
confidence: 99%